Pengaruh Gaya Kepemimpinan Transformasional, Motivasi Dan Fasilitas Sekolah Terhadap Kinerja Guru Di SMK Siti Banun Rantauprapat - Nurmeisyah Hasibuan; Fajar Pasaribu; Hasrudy Tanjung (Forum Kerjasama Pendidikan Tinggi, 2023)
The approach in this study is to use an associative approach, the associative approach is an approach where to find out that there is a relationship or influence between the two variables (the independent variable and the dependent variable). In this study the independent variable X1 is Transformational Leadership Style, X2 is Work Motivation, X3 is School Facilities and the dependent variable Y is Teacher Performance. The data analysis technique starts from collecting information through a questionnaire in the form of a statement and at the final stage by drawing conclusions. Based on the results of the study, it can be concluded that the transformational leadership style has a positive and significant effect on teacher performance at SMK Siti Banun Rantauprapat. In addition, motivation also has a positive and significant effect on teacher performance at SMK Siti Banun Rantauprapat. From the results of further research, it was found that school facilities had a positive and significant effect on teacher performance at SMK Siti Banun Rantauprapat. After that, it was tested simultaneously and it was found that transformational leadership style, motivation and school facilities had a positive and significant effect on teacher performance at SMK Siti Banun Rantauprapat.